Rebranding as an assessment of brand management strategy: the case of Malaysian Government linked companies (GLCS) / Rosni Jaafar - Jaafar, Rosni (Institute of Graduate Studies, UiTM, 2013)
This is an exploratory study about organisations using rebranding as a brand management strategy in Malaysia. It aims to identify motivations or reasons for companies to undertake the rebranding exercise and to determine the stages in the rebranding process. Substantial studies on rebranding have been conducted in Europe and the United States where brand management is an acknowledged strategy for successful businesses. This study seeks to document the reasons for rebranding and stages of the rebranding process of Malaysian companies. A comparison of similarities and differences of the Malaysian rebranding experience with existing studies was conducted. Based on the findings a conceptual framework is proposed…